The effect of strength-endurance training on serum and urine metabolic profiles of female adolescent volleyball athletes - Zhou, W.; Zeng, G.; Lyu, C.; Kou. F.; Zhang, S.; Wei, H. (Physiology International, 2019)
Aim: Limited investigations on metabolic responses to exercise training in female adolescent volleyball athletes exist. The aim of this study was to obtain serum and urine metabolite markers in female adolescent volleyball athletes within 2-week strength-endurance training using a metabolomics approach coupled with biochemical analysis, which would be potential biomarkers for evaluating the physiological state of athletes. Methods: Twelve female adolescent volleyball athletes were recruited for 2-week strength-endurance training. Differential serum and urine metabolic profiles between the pre- and post-training group were obtained on gas chromatography coupled to mass spectrometry (GC-MS) and data subsequently underwent orthogonal partial least-squares analysis (OPLS). Results: Strength-endurance training exerted a significant influence on the athletes' serum and urine metabolic profiles. The changed metabolites were primarily involved in energy metabolism, lipid metabolism and amino acids metabolism. Results support the hypothesis that female athletes displayed an increased propensity to oxidize lipids as the major energy source. Exposure to strength-endurance training also led to a significant increase in cortisol, but a decrease in testosterone, indicating disordered hormone adjustment. Exercise-induced oxidative stress occurred, as was evidenced by the decrease in reduced glutathione, and increases in blood malondialdehyde and oxidized glutathione. Since the muscle damage markers creatine kinase and lactate dehydrogenase did not show significant changes, the training might not cause cell membrane damage and the athletes did not cross the adaptive injury level. Conclusion: By measurement of endogenous metabolites, the metabolomics study has the potential to reveal the global physiological changes in response to exercise training.